Sex differences in large conducting airway anatomy - Dominelli, Paolo B.; Ripoll, Juan G.; Cross, Troy J.; Baker, Sarah E.; Wiggins, Chad C.; Welch, Brian T.; Joyner, Michael J. (Journal of applied physiology (1985), 2018)
Airway luminal area is the major determinant of resistance to airflow in the tracheobronchial tree. Women may have smaller central conducting airways than men; however, previous evidence is confounded by an indirect assessment of airway geometry and by subjects with prior smoking history. The purpose of this study was to examine the effect of sex on airway size in healthy nonsmokers. Using low-dose high-resolution computed tomography, we retrospectively assessed airway luminal area in healthy men ( n = 51) and women ( n = 73) of varying ages (19–86 yr). Subjects with a positive smoking history, cardiopulmonary disease, or a body mass index > 40 kg/m 2 were excluded. Luminal areas of the trachea, right and left main bronchus, bronchus intermediate, left and right upper lobes, and the left lower lobe were analyzed at three discrete points. The luminal areas of the conducting airways were ~26%–35% smaller in women. The trachea had the largest differences in luminal area between men and women (298 ± 47 vs. 195 ± 28 mm 2 or 35% smaller for men and women, respectively), whereas the left lower lobe had the smallest differences (57 ± 15 vs. 42 ± 9 mm 2 or 26% smaller for men and women, respectively). When a subset of subjects was matched for height, the sex differences in airway luminal area persisted, with women being ~20%–30% smaller. With all subjects, there were modest relationships between height and airway luminal area ( r = 0.73–0.53, P < 0.05). Although there was considerable overlap between sexes, the luminal areas of the large conducting airways were smaller in healthy women than in men. NEW & NOTEWORTHY Previous evidence for sex differences in airway size has been confounded by indirect measures and/or cohorts with significant smoking histories or pathologies. We found that central airways in healthy women were significantly smaller (~26%–35%) than men. The significant sex-difference in airway size was attenuated (20%–30% smaller) but preserved in a subset of subjects matched for height. Over a range of ages, healthy women have smaller central airways than men.